The Disposal of Archive in doing its Protection - Lolytasari, - (Record and Library Journal, 2015)
This research discusses about the implication of archieve disposal and explains the existence of the University of Archive which has a function to protect the archive. The problem in this study is how is the application of the archive disposal in State Islamic University that has no retention schedule and the University of Indonesia that has a retention schedule. The objective of this research are (1) to identify the program application of archive disposal in State Islamic University Syarif Hidayatullah Jakarta and the Centre of Archive Administration in the University of Indonesia in protecting the document; and (2) to assess the archive disposal which is done by the Centre of Archive Administration of the University of Indonesia becoming model of archive in the State Islamic University Syarif Hidayatullah Jakarta. The method of the research is descriptive qualitative. The recommendation for this research are; (1) State Islamic University Syarif Hidayatullah Jakarta should develop the unit of archive for university whether it is unit for archive I and unit for archive II which has the function to analyze, to inform, and to protect the archive. The archive can be handled as the accountability evidence for the university. Furthermore, it simplify the information. (2) By the existence of unit for archive I, the State Islamic University Syarif Hidayatullah Jakarta should arrange the guide book of retention schedule as guidance for archive disposal for all units or institutions in State Islamic University Syarif Hidayatullah Jakarta. This guide book will protect the document from the beginning until the end. Moreover, the archivist will not have doubt to dispose uncontrolled archive. In managing the archive, State Islamic University Syarif Hidayatullah Jakarta has to take civil government archivist and professional human resource.